Chronic total ostial occlusion of left main coronary artery in a young lady - report on a rare case - Akanda, MA K; Patwary, MSR; Tanveer, MS; Kar, N; Ulubbi, MS; Rahman, F; Rashid, MA (University Heart Journal, 2008)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–> <!–[if gte mso 10]> <![endif]–> Total ostial occlusion of left main coronary artery is rarely reported atherosclerotic coronary artery disease. This case represents a 27-years young female with no risk factors other than overweight, underwent coronary angiograms, for stable angina with positive stress test at low workload (5-Mets). The angiograms revealed dominant and normal RCA & LCA was visulalized from RCA collaterals up to the proximal part of LMCA with atheromatous plaque in proximal part of LAD & LCX. No antegrade flow was found to visualize left main coronary artery even after root aortogram. Cononary artery bypass graft operation was done and the patient had smooth post operative recovery. Suspicion, diagnosis and revascularization at an early stage is associated with excellent prognosis in terms of symptom free survival. Â Â Â Â Â University Heart Journal Vol.4(1) January 2008 Â